Commius - An email based interoperability solution tailored for SMEs - Burkhart, T.; Werth, D.; Loos, P. (Journal of Digital Information Management, 2008)
More than 99% of European enterprises are SMEs (Small and Medium-sized Enterprises). While in the current market situation collaboration is evolving to an indispensable key factor of success, research is yet to produce results which can be used by SMEs. This paper introduces an interoperability approach in the context of the European Commius Project which enables SMEs collaborate easily on the level of process interoperability. The Commius solution will dock onto existing E-Mail structures and enrich incoming E-Mails with additional information dependant upon its content and provide recommendations of expedient further steps to process the E-Mail. A first picture of the Commius process interoperability layer architecture will be drawn. Furthermore proposals to adapt Commius to the specific processes every SME has, in a simple way, are being exposed.
Keywords: Business process; Collaboration; Email; Interoperability; SME

A generic framework for visualizing the news article domain and its application to real-world data - Lex, E.; Seifert, C.; Kienreich, W.; Granitzer, M. (Journal of Digital Information Management, 2008)
In this work we present APA Labs, a generic framework for visualizing the news article domain. APA Labs is a web-based platform enabling retrieval and analysis of news repositories provided by the Austrian Press Agency. APA Labs is designed as a rich internet application combined with a modular system of interactive visualizations. News articles are analyzed using domain specific named entity extraction methods combined with language specific heuristics. The proposed methods were subject to an evaluation procedure outlined in this contribution. This article illustrates the domain, the underlying concepts and implementation details. Several visualization modules are presented and an outlook on planned modules is given. Being online for around six months the community feedback as well as the easy integration of new modules shows the success of the underlying concept and the platform itself.
Keywords: Business process; Collaboration; Email; Interoperability; SME